By integrating single-cell RNA-seq and bulk RNA-seq in sphingolipid metabolism, CACYBP was identified as a potential therapeutic target in lung adenocarcinoma - Zhang, Pengpeng; Pei, Shengbin; Gong, Zeitian; Feng, Yanlong; Zhang, Xiao; Yang, Fang; Wang, Wei (Frontiers in Immunology, 2023)
Abstract Background: Lung adenocarcinoma (LUAD) is a heterogeneous disease with a dismal prognosis for advanced tumors. Immune-associated cells in the microenvironment substantially impact LUAD formation and progression, which has gained increased attention in recent decades. Sphingolipids have a profound impact on tumor formation and immune infiltration. However, few researchers have focused on the utilization of sphingolipid variables in the prediction of LUAD prognosis. The goal of this work was to identify the major sphingolipid-related genes (SRGs) in LUAD and develop a valid prognostic model based on SRGs. Methods: The most significant genes for sphingolipid metabolism (SM) were identified using the AUCell and WGCNA algorithms in conjunction with single-cell and bulk RNA-seq. LASSO and COX regression analysis was used to develop risk models, and patients were divided into high-and low-risk categories. External nine provided cohorts evaluated the correctness of the models. Differences in immune infiltration, mutation landscape, and immunotherapy were also investigated in distinct subgroups. Finally, cell function experiments were used to investigate the role of CACYBP in LUAD. Results: A total of 334 genes most associated with SM activity were identified for subsequent analysis, and a risk model consisting of 11 genes was finalized by lasso and cox regression. Patients were divided into high-and low-risk groups according to the median risk value, and there were significant differences in tumor immune microenvironment (TIME), mutational landscape, immunotherapy benefit, and pathway activity among different risk groups. It was verified that CACYBP could increase the ability of LUAD cells to proliferate, invade, and migrate. Conclusion: The eleven-gene signature identified in this research may help physicians create individualized care plans for LUAD patients. CACYBP may be a new therapeutic target for patients with advanced LUAD.